Effect Of Product Quality, Price Perception, And Promotion On Purchase Decisions At Pand's Muslim Department Store - Emil Yuliantie (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2021)
This study aims to (1) analyze the effect of product quality on purchasing decisions at Pand's Muslim Department Store. (2) To analyze the effect of price perceptions on purchasing decisions at Pand's Muslim Department Store. (3) Analyzing the effect of promotion on purchasing decisions at Pand's Muslim Department Store. This research model is a quantitative research with data collection techniques using a questionnaire. The sampling technique used purposive sampling. Samples to be taken are respondents who are consumers of Pand's Muslim Department Store. In this study, sampling was carried out by waiting for consumers who had finished making purchases at Pand's Muslim Department Store, consumers who were willing to be respondents, aged over 17 years, and consumers have visited at least 2 times. Data analysis using multiple linear regression. The results showed that (1) Product quality had a positive and significant effect on purchasing decisions, with a significance value of 0.040. (2) Price perception has a positive and significant effect on purchasing decisions, with a significance value of 0.047. (3) Promotion has a positive and significant effect on purchasing decisions, with a significance value of 0.000. (4) Product quality, perceived price, and promotion have a positive and significant effect on purchasing decisions, with a significance value of 0.000. with a significance value of 0.040. (2) Price perception has a positive and significant effect on purchasing decisions, with a significance value of 0.047. (3) Promotion has a positive and significant effect on purchasing decisions, with a significance value of 0.000. (4) Product quality, perceived price, and promotion have a positive and significant effect on purchasing decisions, with a significance value of 0.000. with a significance value of 0.040. (2) Price perception has a positive and significant effect on purchasing decisions, with a significance value of 0.047. (3) Promotion has a positive and significant effect on purchasing decisions, with a significance value of 0.000. (4) Product quality, perceived price, and promotion have a positive and significant effect on purchasing decisions, with a significance value of 0.000.